Implementation Of The Islamic Educational Communication Model In Religious Moderation At The Asahan District Religious Harmony Forum - Muchlis, Sri; Sukiman, Sukiman; Rubino, Rubino (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
The Asahan Regency is home to numerous ethnic and religious groups. This treasure of religious diversity continues to be a source of discord among the populace. Using a communication model based on Islamic education, the Forum for Religious Harmony (FKUB) in Asahan Regency aims to maintain harmony among individuals. This study seeks to examine the religious communication model of FKUB Asahan District, its results in fostering inter-religious harmony among the people of Asahan District, and its impact on fostering inter-religious harmony in Asahan District. According to the findings of the study, the communication model of the Asahan Regency Religious Harmony Forum can be categorized into two situations: the normal situation, which involves socializing and approaching community leaders, religious leaders, and local government officials, and the conflict situation, which involves mediating between conflicting parties. This communication model can prevent human-to-human conflict or quickly resolve existing conflicts, although it does not guarantee the end of human-to-human conflict. This communication model is hindered by a lack of institutional funds to maximize communication, a lack of human resources, and a lack of public time to educate on religious harmony.